The Relationship Between Conformity And Self-Control With Aggressive Behavior In Adolescents - Anggelina Rebecca Elsa Sendow; IGAA Noviekayati; Anrilia E. M Ningdyah (CV. ITTC INDONESIA, 2026)
This study aims to analyze the relationship between conformity and self-control with aggressive behavior in adolescents. Adolescents are a group that is vulnerable to social dynamics and often face challenges in controlling emotional impulses, making aggressive behavior a phenomenon that requires serious attention. This study uses a correlational quantitative approach with multiple linear regression analysis techniques. The research subjects consisted of 396 teenagers in the city of Manado, North Sulawesi, aged between 13 and 18 years. The sample was selected using purposive sampling technique. Data were collected using three psychological scale instruments, namely the Aggression Behavior Scale, the Conformity Scale, and the Self-Control Scale. The research results indicate that there is a significant simultaneous relationship between conformity and self-control with aggressive behavior. Partially, self-control has a significant negative relationship with aggressive behavior, meaning that the higher the self-control ability of adolescents, the lower the tendency to display aggressive behavior. Additionally, a significant negative relationship was found between conformity and aggressive behavior. This indicates that conformity to positive group norms can function as a social control mechanism that suppresses the emergence of aggressive behavior in adolescents. Overall, self-control was found to have a greater contribution in predicting aggressive behavior compared to the conformity variable.